Review of hydraulics of Floating Treatment Islands retrofitted in waterbodies receiving stormwater - Nuruzzaman, M.; Anwar, Faisal; Sarukkalige, Ranjan; Sarker, D.C. (2021)
Stormwater pollution causes an excessive influx of nutrients and metals to the receiving waterbodies (stormwater ponds, lakes, and rivers), which can cause eutrophication and metal toxicity. One of the most cost-effective and eco-friendly solutions to stormwater pollution is constructing Floating Treatment Islands (FTIs) within the waterbodies receiving stormwater runoff. Treatment efficiency of FTIs depends on many factors including plant species, temperature, detention time, and pollutant loading rate. Another important factor is FTI hydraulics, which determines the amount of inflow to the root zone and residence time, greatly impacting the treatment. However, only a few studies refer to the hydraulics of waterbodies retrofitted with FTIs. This paper reviews available literature on field-scale, laboratory-scale and numerical studies on the hydraulics of FTI retrofitted waterbodies. Because of limited knowledge on the factors affecting hydraulics of waterbodies retrofitted with FTIs, current practices cannot ensure maximum hydraulic performance of this system. This review paper identifies different factors affecting the FTI hydraulics, investigates knowledge gaps, and provides future research direction for hydraulically efficient design of FTIs to treat stormwater. It was found that there is a need to investigate the impact of new design parameters such as FTI shape, FTI coverage, inlet-outlet configurations, and shape of waterbody on the hydraulic performance of FTI retrofitted waterbodies. A lack of dimensional analysis on FTI retrofitted waterbodies in existing literature revealed that field-scale values were not properly scaled down in laboratory experiments. Although a few short-circuiting prevention mechanisms (SPMs) were used in different field-scale studies, those mechanisms may be vulnerable to short-circuiting in the vertical dimension. It was revealed that studying the role of eddy diffusion and gap layer for vertical short-circuiting can help designing better SPMs. This review also identified that further investigation is required to incorporate root flexibility in the current modeling approach of FTI retrofitted waterbodies.